2014
DOI: 10.1051/limn/2014091
|View full text |Cite
|
Sign up to set email alerts
|

Are metals in the muscle tissue of Mozambique tilapia a threat to human health? A case study of two impoundments in the Olifants River, Limpopo province, South Africa

Abstract: -Rural communities in South Africa are becoming increasingly reliant on freshwater fish to supplement their dietary protein requirement. Rising costs of other protein sources, increasing rural poverty and escalating rural populations are resulting in increasing consumption of fish from contaminated river systems. The Olifants River, Limpopo Basin, Eastern South Africa, has been systemically impaired and is now one of the most polluted rivers in South Africa. We measured the concentrations of metals in fish mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…The trend of metal concentrations found in the present study confirmed those of previous studies, which showed elevated concentration of Ba, Zn, B, Al, Cu and Fe in the muscle tissues of O. mossambicus and C. gariepinus (Kotze et al 1999;Addo-Bediako et al 2014a;Jooste et al 2015), L. rosae (Jooste et al 2014), Labeo umbratus Smith, 1841 (Coetzee et al 2002) and S. intermedius (Addo-Bediako et al 2014b) in the Olifants River system. The present study found a significant variation in the size of fish from each impoundment.…”
Section: Metal Concentrations In Fish Muscle Tissuesupporting
confidence: 91%
See 3 more Smart Citations
“…The trend of metal concentrations found in the present study confirmed those of previous studies, which showed elevated concentration of Ba, Zn, B, Al, Cu and Fe in the muscle tissues of O. mossambicus and C. gariepinus (Kotze et al 1999;Addo-Bediako et al 2014a;Jooste et al 2015), L. rosae (Jooste et al 2014), Labeo umbratus Smith, 1841 (Coetzee et al 2002) and S. intermedius (Addo-Bediako et al 2014b) in the Olifants River system. The present study found a significant variation in the size of fish from each impoundment.…”
Section: Metal Concentrations In Fish Muscle Tissuesupporting
confidence: 91%
“…Analyses of metals were restricted to 10 metals: aluminium (Al), antimony (Sb), barium (Ba), boron (B), copper (Cu), iron (Fe), lead (Pb), manganese (Mn), strontium (Sr) and zinc (Zn). These metals were selected due to their significant increases recorded over the past decade in the water, sediment and fish tissues from the Olifants River system (Coetzee et al 2002;Addo-Bediako et al 2014a, 2014bJooste et al 2014Jooste et al , 2015. A composite sediment sample consisting of five grab samples was collected from each of the three sites at Flag Boshielo Dam and from two sites at Loskop Dam in May 2011 using a Friedlinger mudgrab.…”
Section: Water and Sediment Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…An important consideration prior to developing a fishery in Flag Boshielo Dam is the potential human health risks associated with the consumption of fish from the Olifants River System. Concentrations of heavy metals that could severely impair human health were found in muscle tissue of S. intermedius (Addo-Bediako et al, 2014b;Marr et al, 2015), O. mossambicus (Addo-Bediako et al, 2014a), L. rosae (Jooste et al, 2014;Lebepe et al, 2016) and C. gariepinus (Jooste et al, 2015;Marr et al, 2015) sampled from Flag Boshielo Dam. For this reason, the development of a fishery might be inappropriate even if catch rates are conducive to fisheries development.…”
mentioning
confidence: 99%